2021
DOI: 10.1152/advan.00226.2020
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions on synchronous virtual versus face-to-face teaching for leader-centered and participant-centered postgraduate activities during COVID-19

Abstract: Consequent to the unprecedented COVID-19 pandemic, pedagogic changes were introduced in postgraduate courses in Physiology, where face-to-face teaching was replaced with synchronous virtual mode for leader-centered (seminar, symposium) and participant-centered (journal club, group discussion) academic activities. We hypothesized that the effectiveness of virtual and face-to-face modes as perceived by postgraduate students in terms of facilitating their overall learning may differ across the spectrum of leader-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
8
0
3
Order By: Relevance
“…In turn, with VIC, large groups with randomly selected participants and social distance between group members might have caused loss of motivation and cooperation, once described as social floating. A previous study supports our findings and reported that students perceived leader-centred virtual activities such as pre-recorded presentations or traditional lecture-style teaching as equally effective, but participant-centred virtual activities such as virtual breakout room discussions with peers as less effective than face-to-face sessions [ 22 ]. Smaller and self-chosen groups as well as an appropriate number of assistant lecturers or student assistants, at least on-demand, for group support would be advantageous [ 18 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…In turn, with VIC, large groups with randomly selected participants and social distance between group members might have caused loss of motivation and cooperation, once described as social floating. A previous study supports our findings and reported that students perceived leader-centred virtual activities such as pre-recorded presentations or traditional lecture-style teaching as equally effective, but participant-centred virtual activities such as virtual breakout room discussions with peers as less effective than face-to-face sessions [ 22 ]. Smaller and self-chosen groups as well as an appropriate number of assistant lecturers or student assistants, at least on-demand, for group support would be advantageous [ 18 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“… 7 Despite students’ broad acceptance of online education formats and their flexibility, others have found that medical trainees still do not favor complete replacement of face-to-face lectures with recorded lectures and report feeling less engaged with such sessions. 8 - 10 Virtual teleconference lectures provide another option for live learning, and students have reported no significant difference in preference between in-person and teleconference formats. 6 , 10 , 11 However, teleconference formats require considerable electronic resources and investment by both trainees and lecturers, and these formats can suffer from audiovisual technical difficulties that can impair the lecture experience.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 10 , 11 However, teleconference formats require considerable electronic resources and investment by both trainees and lecturers, and these formats can suffer from audiovisual technical difficulties that can impair the lecture experience. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it's noted that students' in-class test score under domestic on-site teaching mode was significantly higher than that under international remote teaching mode. This phenomenon may be due to the more active class learning atmosphere or interactions of onsite face-to-face teaching mode compared to distance learning online (17,18). Several studies also emphasized the importance of classroom teaching interactions in the teaching process (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%